Challenges and Adaptations in Remote Teaching: Insights from Rural Educators in Indonesia - Gusti, Valeria Yekti Kwasaning (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2024)
This research focused on the experiences of rural math educators in Indonesia during the pandemic period. The study investigated the challenges encountered by math teachers with varying levels of experience in remote instruction, spanning from beginners to veterans with over 15 years of teaching experience through surveys and interviews. The study utilized a mixed-methods approach which involves combining qualitative and quantitative research methods to achieve a more comprehensive understanding of the challenges encountered by math teachers in remote settings. The findings highlighted common challenges such as poor internet connectivity, limited student access to devices, and decreased student engagement in remote lessons. Despite these challenges, rural math educators have implemented innovative strategies, utilizing diverse online platforms to enhance student participation. Additionally, this study discovered the impact of remote teaching on educators' professional growth as they adapt to new technologies and teaching methods. As schools have transitioned back to in-person learning, the insights underscored the importance of addressing digital disparities and providing educators with the necessary support to navigate future disruptions in the educational landscape.